Distribution and Abundance of Cetaceans in Icelandic Waters over 30 Years of Aerial Surveys - Pike, Daniel G.; Gunnlaugsson, Thorvaldur; Sigurjónsson, Jóhann; Víkingsson, Gísli (NAMMCO Scientific Publications, 2020)
Beginning in 1986, 7 aerial surveys covering the coastal waters of Iceland have been conducted up to 2016. In addition, several partial surveys covering portions of the same area and at different times of the year have been flown in the same 30 year time span. We present previously unpublished abundance estimates, corrected to the extent feasible for known biases, for common minke whales (Balaenoptera acutorostrata), humpback whales (Megaptera novaeangliae), white-beaked dolphins (Lagenorhynchus albirostris) and harbour porpoises (Phocoena phocoena) from some or all of the 2007, 2009 and 2016 surveys. The relative abundance of most species was comparatively low in the spring and fall, and peaked June and July when all of the main surveys have been carried out. An analysis of changes in line transect density as an index of relative abundance from all surveys indicates that common minke whale abundance decreased by 75% after 2001 and has remained at a relatively low level since then. Relative abundance of humpback whales and white-beaked dolphins has increased over the period 1986-2016. We place these observed changes in context with oceanographic and ecosystem changes documented over the same period.